PENDIDIKAN ISLAM DAN DAKWAH PEREMPUAN DI PERKOTAAAN: AISYIYAH JAKARTA SELATAN - Ai Fatimah Nur Fuad (Jurnal Pendidikan Islam, 2020)
Women's participation in da'wa activities in the community has been widely studied. Likewise with the contribution of their involvement in various da’wa movements or Islamic organizations. This research aims to strengthen the existing studies, with a focus on the Aisyiyah da’wa community in urban areas. Specifically, this research seeks to investigate how inclusive and solutive the da'wa community is in carrying out its various activities among the Ulujami community in South Jakarta. This research was assessed using a qualitative approach that is not only by conducting relevant literature reviews but also by conducting in-depth interviews with leaders and members of the Aisyiyah branch of Ulujami, and the female community who reside and participate in various activities of Aisyiyah Ulujami-South Jakarta. In addition, participant observation were also conducted to look closely variety of their da’wa activities, ranging from religious education for empowering people and strengthening their religiosity to health services for helping people around them. The result of this research conducted in 2019 and early 2020 shows that the variety of activities carried out by Aisyiyah Ulujami in the middle of the Betawi urban community has made significant social contributions, especially in terms of women's empowerment related to strengthening religious insight, awareness to maintain health and strengthening social harmony in the midst of pluralistic society. This research could contribute to the discourses of the activities of female da'wa community in urban areas and its influences to the wider female community and society in general.